Antioxidant and hepatoprotective activity of Flemingia tuberosa Dalzell in CCl4-induced hepatotoxicity in rats - Reena William Mascarenhas, Sunita Shailajan, Sasikumar Menon (Journal of Applied Pharmaceutical Science, 2020)
Flemingia tuberosa Dalzell is an endemic species of the Western Ghats. It is an ethnomedicinal plant used to cure dysentery and vaginal discharge. However, in this study, the hepatoprotective potency of the plant has been evaluated as it contains flavonoids like kaempferol. The present study was conducted to investigate the hepatoprotective activity of the ethanolic extract of aerial parts of F. tuberosa against Carbon tetrachloride (CCl4)-induced toxicity in rats. The extract was standardized using a validated HPTLC method for kaempferol content. The antioxidant activity of the ethanolic extract of aerial parts of F. tuberosa was assessed by 1,1-diphenyl-2-picrylhydrazyl method. The hepatoprotective activity was assessed against CCl4-induced liver intoxication, wherein the CCl4-induced albino Wistar rats were treated with three different doses of the standardized extract for 3 days. The results were compared with the established positive control, Silymarin. The protective effect on the liver was also monitored histopathologically using light and electron microscope and biochemically through observing the levels of biochemical enzymes. The extract showed potent hepatoprotective activity. This study confirms the protective effect of the ethanolic extract of aerial parts of F. tuberosa against CCl4-induced hepatotoxicity.
Keywords: Flemingia, endemic, chromatography, antioxidant, hepatoprotective, histopathology.